2020
DOI: 10.1088/1757-899x/870/1/012125
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of “Text Steganography Based on Unicode of Characters in Multilingual” by Custom Font with Special Properties

Abstract: Since computer utilization is expanding, for both social and trade ranges, secure communications through channels got to be an exceptionally critical issue. Information hiding away could be a strategy to get a secure communication medium and securing the data amid transmission. Text documents have very less redundant information as compared to the images and audio, therefore, text steganography is most challenging. This paper aims to improve “text steganography based on Unicode of characters in multilingual” b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…By comparison, the Arabic language uses points, word diacritics, and Kashida. For the English language, as seen in [40,[44][45][46]53,55], various language attributes are used, such as the font, capital and lower-case letters, double letters, high-frequency letters, punctuation, and other symbols. Secret messages are also hidden according to the shape of the English capital alphabets by dividing the letters into groups depending on the letter's shape (curved, vertical, horizontal, etc.).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, the Arabic language uses points, word diacritics, and Kashida. For the English language, as seen in [40,[44][45][46]53,55], various language attributes are used, such as the font, capital and lower-case letters, double letters, high-frequency letters, punctuation, and other symbols. Secret messages are also hidden according to the shape of the English capital alphabets by dividing the letters into groups depending on the letter's shape (curved, vertical, horizontal, etc.).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Ref. [45] suggested a technique to enhance the embedding capacity for format-based text steganography using the font and other text characteristics for encoding secret information. This technique uses similar symbols for several codes, known as Set of High-Frequency Letters (SHFLs), used for embedding.…”
Section: Format-based Methodsmentioning
confidence: 99%
“…In this section we will investigate some of steganograpgy methods that are related to our work. Shakir and Abdulameer [11] suggested that a new font with special properties be developed for data hiding purposes. Furthermore, for the embedding process, the set of high-frequency letters called SHFL in the English language was chosen based on making the same glyphs for the multiple codes.…”
Section: Related Workmentioning
confidence: 99%
“…Our method is also characterized by a high degree of security, which was increased by encryption, and then the message was included with the confidential message in the cover text. [11] Low Invisible High Unispach and ZeroWidth [12] High Invisible High EM_ST [13] High Visible Low 4&3SpaCh [14] High Invisible Medium ZW-4B [15] Low Invisible Medium UniSpaCh [16] Low Invisible Medium Stojanov [17] High Invisible Low…”
Section: Capacity Ratio = (Stego Text Size) / (Stego Text Size After Compression) …………(2)mentioning
confidence: 99%
“…[3]. Text steganography is mainly divided into two categories: formatbased methods and content-based ones [4]. Format-based methods use special characters, line-shifting, and wordshifting to code the text [5].…”
Section: Introductionmentioning
confidence: 99%